Correction: Exploring the optimal ratio of elemental components of the Cu/SSZ-13 framework: the reformation of NH3-SCR properties. (28th July 2022) - Liu, Ziqian; Guan, Bin; Jiang, Han; Wei, Yanfei; Wu, Xingze; Zhou, Jiefei; Lin, He; Huang, Zhen
Abstract : Correction for 'Exploring the optimal ratio of elemental components of the Cu/SSZ-13 framework: the reformation of NH3 -SCR properties' by Ziqian Liu et al., New J. Chem., 2022, 46, 13593–13607, ; https://doi.org/10.1039/D2NJ01132H .